Adding Concurrent Chemotherapy to Intensity-Modulated Radiotherapy Does Not Improve Treatment Outcomes for Stage II Nasopharyngeal Carcinoma: A Phase 2 Multicenter Clinical Trial - Huang, Xiaodong; Chen, Xiaozhong; Zhao, Chong; Wang, Jingbo; Wang, Kai; Wang, Lin; Miao, Jingjing; Cao, Caineng; Jin, Ting; Zhang, Ye; Qu, Yuan; Chen, Xuesong; et al. (Frontiers in Oncology, 2020)
Purpose: To explore the efficacy of concomitant chemotherapy in intensity-modulated radiotherapy(IMRT) to treat stage II nasopharyngeal carcinoma (NPC). Methods and Materials: In this randomized phase 2 study (registered with ClinicalTrials.gov, (NCT01187238)), eligible patients with stage II (2010 UICC/AJCC) NPC were randomly assigned to either IMRT alone (RT group) or IMRT combined with concurrent cisplatin (40 mg/m2, weekly) (CCRT group). The primary endpoint was overall survival (OS). The second endpoints included local failure-free survival (LFFS), regional failure-free survival (RFFS), disease-free survival (DFS), distant metastasis-free survival (DMFS), and acute toxicities. Results: Between May 2010 to July 2012, 84 patients who met the criteria were randomized to the RT group (n = 43) or the CCRT group (n = 41). The median follow up time was 75 months. The OS, LFFS, RFFS, DFS, and DMFS for the RT group and CCRT group were 100% vs. 94.0% (p = 0.25), 93.0% vs. 89.3% (p = 0.79), 97.7% vs. 95.1% (p = 0.54), 90.4% vs. 86.6% (p = 0.72), and 95.2% vs. 94.5% (p = 0.77), respectively. A total of 14 patients experienced disease failure, 7 patients in each group. The incidence of grade 2 to 4 leukopenia was higher in the CCRT group (p = 0.022). No significant differences in liver, renal, skin, or mucosal toxicity was observed between the two groups. Conclusion: For patients with stage II NPC, concomitant chemotherapy with IMRT did not improve survival or disease control and but had a detrimental effect on bone marrow function.